Unveiling Feminist Themes: Simone de Beauvoir’s Influence on The Book Little Women - Aeniaska, Nanda Putri; Agung, I Gusti Ayu Mahatma; Sosiowati, I Gusti Ayu Gde (Prominent, 2025)
From a feminist standpoint, this article examined Louisa May Alcott's Little Women with a perspective on issues such as the complexity of womanhood, existential independence, personal choice, and the continuous fight against objectification. This study, using a qualitative method, examined how the characters, especially the March sisters, negotiate the gender roles imposed upon them in 19th-century society. Every sister has a different reaction to the cultural standards of femininity, and their experiences expose the restrictions placed by social roles. Jo's defiance of conventional wisdom, particularly her refusal to marry for convenience and her will to be a writer, questions the belief that a woman's fate rests just in marriage and housekeeping. Marmee also stresses over simple social compliance the value of financial independence and personal conviction. These character paths highlight how women try to establish autonomy inside limited systems and reflect more philosophical questions about freedom, choice, and identity. Little Women challenges the cultural narratives that try to define and restrict women in other ways than telling a coming-of-age story through its subtle representations. This study highlights the continuing importance of the work and shows how literature can be an important lens through which feminist issues, especially the complexity of gendered experience may be explored and understood.